Comparison of modern and ancient barite‐bearing acid‐sulphate soils using micromorphology, geochemistry and field relationships. Issue 4 (14th February 2015) - Jennings, Debra S.; Driese, Steven G.; Dworkin, Stephen I.; Sheldon, Nathan
Abstract Although pedogenic barite has been documented in many modern soils and palaeosols, no actualistic studies on its formation have been reported. Because barite is stable over the entire range of pressure and temperature of the Earth's crust, it preserves reliable data about the original environment in which it formed. Pedogenic barite and barite‐bearing soils have been used as indicators of landscape stability, environmental conditions, climate and microbial acti‐vity. This study compares field data, micromorphology and stable isotope geochemistry of a barite‐bearing palaeosol from the Morrison Formation (Jurassic) and a modern analogue soil in south‐central Texas, USA. Morrison barite‐bearing palaeosols are over‐thickened cumulic palaeosols that developed in subaerially exposed lacustrine sediments during an extended lake contraction event. Lateral facies relationships document changes in hydrology and duration of episaturated conditions (perched water table above the Btg horizons) that correspond to differences in barite nodule morphology and abundance. Barite precipitation occurred at a redox boundary higher on the landscape after organic matter was completely oxidized. Sulphur isotope data indicate that the initial source of sulphur was soil organic matter. Meteoric water is the likely source of oxygen for the sulphate. Barium sourced from weathering feldspars and clays. The modern analogue displays similar catenary relationships, redox features and micromorphological characteristics compared to the Morrison palaeosols, suggesting that similar pedogenic processes led to barite precipitation. Synthesized data suggest that conditions favourable to barite‐bearing soil formation are low‐gradient basins that have received feldspar‐rich sediments (i.e. volcanically influenced basins), soils that developed near salt domes, soils that developed in exposed wetland or lacustrine sediments and coastal plain deposits. When studied in a well‐documented palaeogeographic context, barite‐bearing soils are valuable to palaeoclimate, palaeoenvironmental and palaeohydrological studies. Combined with regional interfluve palaeosols, barite‐bearing palaeosols may document temporal changes in drainage, surface stability, and accommodation consistent with sequence boundaries/maximum flooding surfaces and climate changes.